Human RTEL1 Interacts with KPNB1 (Importin β) and NUP153 and Connects Nuclear Import to Nuclear Envelope Stability in S-Phase - Michael Schertzer; Laurent Jullien; André Luiz Pinto Santos; Rodrigo T. Calado; Patrick Revy; Arturo Londoño‐Vallejo (2023)
Regulator of TElomere Length Helicase 1 (RTEL1) is a helicase required for telomere maintenance and genome replication and repair. RTEL1 has been previously shown to participate in the nuclear export of small nuclear RNAs. Here we show that RTEL1 deficiency leads to a nuclear envelope destabilization exclusively in cells entering S-phase and in direct connection to origin firing. We discovered that inhibiting protein import also leads to similar, albeit non-cell cycle-related, nuclear envelope disruptions. Remarkably, overexpression of wild-type RTEL1, or of its C-terminal part lacking the helicase domain, protects cells against nuclear envelope anomalies mediated by protein import inhibition. We identified distinct domains in the C-terminus of RTEL1 essential for the interaction with KPNB1 (importin β) and NUP153, respectively, and we demonstrated that, on its own, the latter domain can promote the dynamic nuclear internalization of peptides that freely diffuse through the nuclear pore. Consistent with putative functions exerted in protein import, RTEL1 can be visualized on both sides of the nuclear pore using high-resolution microscopy. In all, our work points to an unanticipated, helicase-independent, role of RTEL1 in connecting both nucleocytoplasmic trafficking and nuclear envelope integrity to genome replication initiation in S-phase.